2015
DOI: 10.1016/j.pharmthera.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

CD70: An emerging target in cancer immunotherapy

Abstract: Over the last decades, advances in the knowledge of immunology have led to the identification of immune checkpoints, reinvigorating cancer immunotherapy. Although normally restricted to activated T and B cells, constitutive expression of CD70 in tumor cells has been described. Moreover, CD70 is implicated in tumor cell and regulatory T cell survival through interaction with its ligand, CD27. In this review, we summarize the targetable expression patterns of CD70 in a wide range of malignancies and the promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 97 publications
4
150
1
Order By: Relevance
“…The CD70/CD27 pathway is currently an area of interest [58]. CD70 is implicated in tumour cell and regulatory T cell survival through interaction with its ligand CD27 [58].…”
Section: Pd-1 or Pd-l1 Blockade In Combination With Other Adaptive Immentioning
confidence: 99%
See 1 more Smart Citation
“…The CD70/CD27 pathway is currently an area of interest [58]. CD70 is implicated in tumour cell and regulatory T cell survival through interaction with its ligand CD27 [58].…”
Section: Pd-1 or Pd-l1 Blockade In Combination With Other Adaptive Immentioning
confidence: 99%
“…CD70 is implicated in tumour cell and regulatory T cell survival through interaction with its ligand CD27 [58]. Combining CD70-CD27 blockade with other immune checkpoint inhibitors might enhance anticancer immune responses [58]; Phase I trials are currently ongoing ( …”
Section: Pd-1 or Pd-l1 Blockade In Combination With Other Adaptive Immentioning
confidence: 99%
“…Studies on CD70 expression revealed the same restricted expression profile in both humans and mice (9, 10), with CD70 only found on a small percentage of activated T cells and antigen presenting cells in draining lymph nodes during viral infection (10). Interestingly, a number of human tumors can also express CD70 including solid cancers such as clear cell renal cancer (RCC), glioblastoma, and hematological malignancies (11-14). The mechanism of overexpression of CD70 on tumors remains unknown, but a recent study suggested the dysregulated pVHL/HIF pathway may be involved in RCC (15).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, there is no uniform reporting of CD70 IHC in malignancies in the literature. The use of different methods (formalin-fixed paraffin-embedded or frozen-section), different antibody clones and different thresholds for positivity make it impossible to compare these results [8]. Moreover, as demonstrated here, different cellular expression patterns of CD70 can be discerned, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, CD70 expression has been reported in a variety of human malignancies (e.g. lymphoma, leukemia, renal cell carcinoma and nasopharyngeal carcinoma) [8]. In this context, CD70 contributes to an immunosuppressive microenvironment by augmenting and/or attracting regulatory T cells, inducing T cell apoptosis and stimulating T cell exhaustion [9,10,11].…”
Section: Introductionmentioning
confidence: 99%